Public-Private Entanglement: Entrepreneurship in a Hybrid Political Order, the Case of Lebanon - Nora Stel; Wim Naudé (Institute for the Study of Labor (IZA), 2013)
The instability and informality that characterize hybrid political orders and its effects on entrepreneurs remains largely unexplored in the scholarly literatures. In this paper we provide initial findings from the case of entrepreneurs' access to electricity in Lebanon. Using quantitative and qualitative methods we find that political connections significantly influence the investment decisions of entrepreneurs and the performance of their firms. In general, a hybrid political order imposes a 'tax' on entrepreneurship by channelling entrepreneurial talent into lobbying and bribery; by reinforcing male and family-owned dominance in business; and by skewing investment decisions. Specifically, we find that family firms whose entrepreneurs engage in bribery, and who obtain government contracts alleviate electricity problems and perform better.
Keywords: L26; M48; O17; O53; 330; entrepreneurship; development; political economy; electricity; infrastructure; Middle East; Lebanon; hybrid political order